Ageism: considerations based on knowledge among undergraduate students and speech therapists (Research, Society and Development, 2021)
Literature suggests that negative attitudes toward the elderly may have adverse effects, especially in health care settings and in rehabilitation. Little is known about the knowledge of speech therapists about the aging process. The purpose of this investigation was to examine the knowledge about aging in professionals and a group of undergraduate students enrolled in an accredited speech-language pathology program to determine if the degree of ageism differed based on gender, age or previous experience working with older adults. This is a descriptive cross-sectional study with 102 students and 120 speech therapy professionals. Data were collected through a sociodemographic questionnaire and a questionnaire to assess gerontological knowledge (adapted by Kosh et al 2007 from the "Palmore Aging Quiz"). The data was analyzed using descriptive statistics and analysis odds ratio calculated for effect size between groups.  A higher prevalence of students who do not have knowledge about aging process is observed. Regarding  questions about age process a higher prevalence of students who do not have knowledge about the aging process is observed. There was no significant effect for the descriptive variables such as living with the elderly, work or academic experience about not having knowledge about aging, for each of the 23 questions among students and speech therapists.